The toughest transistor yet [GaN transistors]. - Eastman, L.F.
GaN transistors withstand extreme heat and are capable of handling frequencies and power levels well beyond those possible with silicon, gallium arsenide, silicon carbide, or essentially any other semiconductor yet fabricated. Frequency and power-handling capabilities of this caliber could make all the difference in amplifiers, modulators, and other key components of the advanced communications networks. GaN transistors could double or triple the efficiency of base-station amplifiers, so that a given area could be covered by fewer base stations or, more likely, be flooded with more data at much higher rates. These same characteristics of speed, high-power handling, and heat resistance would also suit the transistors for many other uses
Keywords: GaN; GaN transistors; Advanced communications networks; Broadband wireless networks; Cellular base-station amplifiers; Electron mobility; Field-effect transistor; Heat resistance; High breakdown field; High frequency handling; High speed; High-frequency characteristics; High-power handling; Hybrid electric vehicles